(untitled) (Research, Society and Development, 2021)
Dragonfly immatures are found in a vast number of freshwater aquatic environments, including excavated tanks of pisciculture. As they are predators during the aquatic phase, they end up causing great damage in the initial stages of production of freshwater aquaculture. However, studies on which dragonflies are most common in fish ponds are still scarce in Brazil, and this is the first step to think about an effective control. For this reason, we collected immature dragonfly (Odonata) with net "D" and macrophytes between October 218 and March 2019. The physicochemical variables were measured with water quality kits, and they remained within the parameters for fish farming defined by CONAMA, with the exception of temperature. Of the 692 immatures collected, we found 12 genera distributed in the two suborders of Odonata, with Miathyria Kirby, 1889 and Erythemis Hagen, 1861 being the most abundant. After correspondence analysis and principal component analysis, we proved that rarer genera have a lower correlation with abundance, reinforcing the value attributed to the relative abundance of immatures.